On the calculation of steady-state loss probabilities in the GI/G/2/0 queue. (1994) - Kovalenko, Igor N.; Atkinson, J. Ben
Abstract : This paper considers methods for calculating the steady-state loss probability in the G I / G / 2 / 0 queue. A previous study analyzed this queue in discrete time and this led to an efficient, numerical approximation scheme for continuous-time systems. The primary aim of the present work is to provide an alternative approach by analyzing the G I / M E / 2 / 0 queue; i.e., assuming that the service time can be represented by a matrix-exponential distribution. An efficient computational scheme based on this method is developed and some numerical examples are studied. Some comparisons are made with the discrete-time approach, and the two methods are seen to be complementary.